Cover Picture: Plasmon‐Enhanced Fluorescence Resonance Energy Transfer (Chem. Rec. 5/2019). Issue 5 (10th May 2019) - Zong, Huan; Wang, Xinxin; Mu, Xijiao; Wang, Jingang; Sun, Mengtao
Abstract : The cover picture shows the physical mechanism of surface plasmon‐enhanced fluorescence resonance energy transfer (PE‐FRET). The fluorescence of the donor is greatly increased by surface plasmon resonance. Secondly, the plasmon‐enhanced fluorescence of the donor is significantly absorbed by the acceptor via PE‐FRET, and then further enhanced fluorescence of the acceptor by surface plasmon resonance. See the Personal Account by J. Wang, M. Sun et al. (DOI:10.1002/tcr.201800181 ).